Tiroides y depresión. Enfoque terapéutico actual y bases moleculares - Liberman G., Claudio; Risco N., Luis; Massardo V., Teresa; Araya Q., Verónica; Fiedler T., Jenny; Jaimovich F., Rodrigo; Galleguillos U., Tamara (Revista Hospital Clínico Universidad de Chile, 2007)
Depression is a serious and high-priority public health problem. In Chilean population, prevalence ranges from 5 to 27,3%. Therapy is based mainly in the use of selective serotonin reuptake inhibitors (SSRIs). Combination of thyroid hormone, sodium liothyronine, associated to traditional antidepressants to improve or accelerate therapeutic response is currently accepted. The use of this combination is based on hypothalamus-hypophysis-thyroid axis (HHT) alterations and on the peripheral conversion to active hormone, the triiodothyronine (T3), by type 2 and 3 deiodinases (D2 and D3). Subtle changes in enzyme activity could have a strong impact in T3brain availability. In major depression as high as a 25% of altered responses of HHT axis to the TRH stimulus may be observed. Certain polymorphisms of the D2 gene could be associated to enzyme activity changes. Isotopic studies are able to assess brain flow in diverse conditions, like global or specific regional perfusion variations in patients with mild hypothyroidism, pre and post T4 or SSRIs therapy in depressive patients.